5=(-z+3)

Simple and best practice solution for 5=(-z+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5=(-z+3) equation:


Simplifying
5 = (-1z + 3)

Reorder the terms:
5 = (3 + -1z)

Remove parenthesis around (3 + -1z)
5 = 3 + -1z

Solving
5 = 3 + -1z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add 'z' to each side of the equation.
5 + z = 3 + -1z + z

Combine like terms: -1z + z = 0
5 + z = 3 + 0
5 + z = 3

Add '-5' to each side of the equation.
5 + -5 + z = 3 + -5

Combine like terms: 5 + -5 = 0
0 + z = 3 + -5
z = 3 + -5

Combine like terms: 3 + -5 = -2
z = -2

Simplifying
z = -2

See similar equations:

| 4x^2+9y^2-16x+18y=11 | | 2x+x=25+2 | | 2x^2-8x+10=x^2+2x-6 | | 6m+8=2m+32 | | x^3-2x^2-5x-6= | | (7n-6)(n+7)=0 | | .948=.75x-ln(x) | | 20=67-f | | .948=.75x-lnx | | (3x-16)=x | | 13q-11q-q=12 | | 10+3(4x-2)=-32 | | 10+44=10k-10 | | 8x+5x-15=9x-6x-1 | | 6x(x-2)= | | 2+2(5x-4)=7-5(2x+1) | | Y/3=96 | | 3n^2+24=22n | | 3.4/3 | | 3x+3[5x-7x]=12-x | | 31+z=13 | | M-87=101 | | 71/2-11/12 | | 35+x=43 | | 6.25=r | | 5n+7=6 | | -x(-x+5)=36 | | 40x^2+30x=10x | | X^2=40+3x | | 8+3(4x-5)=6-4(2x+1) | | 1/2(7x-2) | | 19=2w-17 |

Equations solver categories